2022
DOI: 10.3390/polym14071343
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Silk Fibroin Materials for Biomedical Applications—A Review

Abstract: This review provides a report on recent advances in the field of chitosan (CTS) and silk fibroin (SF) biopolymer blends as new biomaterials. Chitosan and silk fibroin are widely used to obtain biomaterials. However, the materials based on the blends of these two biopolymers have not been summarized in a review paper yet. As these materials can attract both academic and industrial attention, we propose this review paper to showcase the latest achievements in this area. In this review, the latest literature rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 185 publications
0
12
0
Order By: Relevance
“…Chitosan can be modified by covalent crosslinking to fix its low solubility in natural pH and low mechanical properties. The swelling sensitivity of ionically crosslinked chitosan hydrogels to changes in pH is greater than that of covalently crosslinked chitosan hydrogels, which extends the potential application of ionically crosslinked chitosan hydrogels [16].…”
Section: Fig 2: Chitosan Structure [14]mentioning
confidence: 85%
See 1 more Smart Citation
“…Chitosan can be modified by covalent crosslinking to fix its low solubility in natural pH and low mechanical properties. The swelling sensitivity of ionically crosslinked chitosan hydrogels to changes in pH is greater than that of covalently crosslinked chitosan hydrogels, which extends the potential application of ionically crosslinked chitosan hydrogels [16].…”
Section: Fig 2: Chitosan Structure [14]mentioning
confidence: 85%
“…The biochemical tests showed that chitosan/silk fibroin material improved cell attachment and proliferation [16,37].…”
Section: Cs-sf Composites Nanofibersmentioning
confidence: 99%
“…Moreover, silk can be also used together with another polymer forming the polymer blend. [115][116][117][118] Elahi et al 119 mentioned that pure silk broin as a blood contacting material was not a better choice due to lack of good hemocompatibility. The aim of enhanced hemocompatibility of silk broin can be achieved by varying the surface properties of silk broin.…”
Section: Proteinsmentioning
confidence: 99%
“…Chitosan is commonly found in the outer protective shells of invertebrates and possesses good biocompatibility, biodegradability, nontoxicity, and various physiological functions such as antibacterial, hypocholesterolemic, anticancer, and immune enhancement properties . Chitosan itself is used in many fields, such as beauty care, cosmetics, antimicrobial agents, medical fibers, medical dressings, artificial tissue materials, drug slow-release materials, gene transfer carriers, biomedical fields, medical absorbable materials, tissue engineering carrier materials, medical treatment, and drug development. Chitosan can form hydrogels by changing pH and temperature and can be degraded in vivo by lysozyme and diacetyl chitosanase, thus forming gels that can be applied in living organisms. Chitosan-based hydrogels have been widely used in controlled drug release, artificial tissues, cartilage repair, medical coatings, and tumor therapy. …”
Section: Overview Of Polysaccharide-based Polymers and Their Propertiesmentioning
confidence: 99%